Regolith Landform Unit Mapping using Hyperspectral Imaging (Case study: Block G TickHill Mt.Isa, Australia) - Agustin, Fitriani (Pusat Survei Geologi, 2016)
The advent of new hyperspectral has improved the rapid surface mapping of minerals and earth materials. This research is creating the mineral maps using HyMap in Tick Hill Mount Isa Northwest Queensland as a guide for the regolith landform unit mapping.Tick Hill area is part of the Proterozoic Eastern and Western Fold Belt Province of Mt.Isa Inlier Complex. The areas were covered by Mesozoic and Paleozoic lithologies dominated by medium to coarse hornblende-biotite granite and gneiss intruded during 1760 – 1720Ma. Highly weathered landform covered the whole area. The Mesozoic sediments have experienced to deep weathering currently present in the form of mesas. The weathering profiles are dominated by kaolinite, smectite, and pedogenic carbonates with some secondary silicification. Part of the landform was covered by colluvium which varied in thickness from less than 1 meter to up to 12 meter in certain places.The general image processing for HyMap has been done for the area. In addition, ASD spectra laboratory has been applied to validate the remotely sensed mineral information. Iron Oxide and Al-OH (kaolinite, illite, smectite) mineral maps have been successfully created through HyMap imagery. Those can easily identified through the band ratio with some mask application (relative band depth method) in HyMap. For final process, GIS method is used to overlay all the data producing regolith landform unit map. AL-OH mainly kaolinite mineral map is showing the usefulness for identification the surface regolith mapping (mottle zone) and its crystallinity maps can differentiate transported and in situ regolith materials. In addition, Iron oxide map is able to identify ferruginous and laterite surface materials.Keywords: HyMap,Regolith,Mineral Mapping, TickHill,Mt.Isa